The Role of the GH/IGF1 Axis on the Development of MAFLD in Pediatric Patients with Obesity - Antonella Mosca; Luca Della Volpe; Anna Alisi; Nadia Panera; Giuseppe Maggiore; Andrea Vania (Metabolites, 2022)
The anomalies of the Growth Hormone (GH)/Insulin-like Growth Factor-1 (IGF1) axis are associated with a higher prevalence of Metabolic Associated Fatty Liver Disease (MAFLD) and with a more rapid progression towards fibrosis, cirrhosis, and end-stage liver disease. A total of 191 adolescents with obesity [12–18 years] were consecutively enrolled between January 2014 and December 2020 and underwent liver biopsy to diagnose MAFLD severity. In all patients GH, IGF1 and Insulin-like Growth Factor-Binding Protein 3 (IGFBP3) were measured. Patients with inflammation and ballooning have significantly lower values of GH and IGF1 than those without (GH: 5.4 vs. 7.5 ng/mL; IGF1 245 vs. 284 ng/mL, p < 0.05). GH and IGF1 were also negatively correlated with fibrosis’ degree (r = −0.51, p = 0.001, and r = −0.45, p = 0.001, respectively). Only GH correlated with TNF-a (r = −0.29, p = 0.04) and lobular inflammation (r = −0.36, p = 0.02). At multivariate regression, both GH and IGF1 values, after adjustment for age, sex and BMI, were negatively associated with HOMA-IR but above all with fibrosis (GH→β = −2.3, p = 0.001, IGF1→β = −2.8, p = 0.001). Even in the pediatric population, a reduction of GH input in the liver directly promotes development of de novo hepatic lipogenesis, steatosis, fibrosis and inflammation. The possible role of recombinant GH administration in adolescents with obesity and severe MAFLD deserves to be studied.